Metabolic trajectories across early adolescence: differences by sex, weight, pubertal status and race/ethnicity - Wei Perng; Sheryl L. Rifas-Shiman; Marie-France Hivert; Jorge E. Chavarro; Joanne Sordillo; Emily Oken (Taylor & Francis Group, 2019)
Background: Biomarkers of cardiovascular and metabolic risk track from adolescence into adulthood, therefore characterising the direction and magnitude of these changes is an important first step to identifying health trajectories that presage future disease risk. Aim: To characterise changes in metabolic biomarkers across early adolescence in a multi-ethnic cohort. Subjects and methods: Among 891 participants in Project Viva we estimated changes in insulin resistance (HOMA-IR), adipokines, lipids, and SBP between ages 6-10 years and 11-16 years. Next, we used multivariable linear regression to examine associations of sex, baseline overweight/obesity, baseline pubertal status and race/ethnicity with change in the biomarkers during follow-up. Results: Boys exhibited a larger decrement in adiponectin (−0.66 [95% CI = −1.14, −0.18)] ng/mL) and a greater increase in SBP (3.20 [2.10, 4.30] mmHg) than girls. Overweight/obese participants experienced larger increases in HOMA-IR, leptin, and triglycerides; and a steeper decrement in HDL. Pubertal youth showed larger decrements in total and LDL cholesterol than their pre-pubertal counterparts. In comparison to White participants, Black youth experienced a larger magnitude of increase in HOMA-IR, and Hispanic youth exhibited larger decrements in adiponectin and HDL. Conclusions: Change in metabolic biomarkers across early adolescence differed by sex, weight status, pubertal status and race/ethnicity. Some of the metabolic changes may reflect normal physiological changes of puberty, while others may presage future disease risk. Future studies are warranted to link metabolic changes during adolescence to long-term health.